2004
DOI: 10.1002/ejlt.200300906
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and postprandial lipid metabolism – an analysis of the current evidence

Abstract: Exercise and postprandial lipid metabolism -an analysis of the current evidenceExaggerated levels of postprandial lipaemia are implicated in the atherosclerotic disease process and are a risk marker for cardiovascular disease. Postprandial lipaemia is reduced following an exercise session and the energy expended during exercise is an important determinant of the extent of triglyceride (TG) lowering. Interestingly, the TGlowering effect of an exercise session cannot be replicated by restricting energy intake to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 107 publications
0
17
0
1
Order By: Relevance
“…As increased chylomicronlike TG clearance is largely the consequence of increased LPL activity, the relationship between chylomicron-like-TG clearance and post-heparin LPL activity is very strong (12,36), the latter observation (i.e., lower TG concentrations despite similar chylomicron-like TG clearance) (21) suggests that mechanisms other than increased LPL activity are likely to also contribute to the TG-lowering effect of exercise. Indeed, a number of studies have demonstrated a dissociation between TG lowering and increased LPL activity following exercise (22). In the present study, the 43% increase in Intralipid-TG FCR in response to 2 h of walking is likely to reflect increased LPL activity, although exercise-induced changes in blood perfusion of LPL-rich tissues resulting in increased interactions between Intralipid-TG and LPL could conceivably have also contributed (30).…”
Section: Discussionmentioning
confidence: 50%
“…As increased chylomicronlike TG clearance is largely the consequence of increased LPL activity, the relationship between chylomicron-like-TG clearance and post-heparin LPL activity is very strong (12,36), the latter observation (i.e., lower TG concentrations despite similar chylomicron-like TG clearance) (21) suggests that mechanisms other than increased LPL activity are likely to also contribute to the TG-lowering effect of exercise. Indeed, a number of studies have demonstrated a dissociation between TG lowering and increased LPL activity following exercise (22). In the present study, the 43% increase in Intralipid-TG FCR in response to 2 h of walking is likely to reflect increased LPL activity, although exercise-induced changes in blood perfusion of LPL-rich tissues resulting in increased interactions between Intralipid-TG and LPL could conceivably have also contributed (30).…”
Section: Discussionmentioning
confidence: 50%
“…Thus the favourable lipoprotein profile evident in regular exercisers is likely to be mainly as a consequence of repeated acute effects of single exercise sessions on TG metabolism. A detailed evaluation of this topic is beyond the scope of the present review and for a detailed overview the reader is directed to recent reviews by Gill [55] and Gill and Hardman [50].…”
Section: Figure 2 Mechanisms By Which Physical Activity Is Likely To mentioning
confidence: 99%
“…56 The chief mechanism for this effect is the lipoprotein lipase-induced clearance of TG-rich lipoproteins, along with a possible reduced hepatic synthesis associated with exercise training. 57 (Table 1 summarizes changes associated with exercise. )…”
Section: Exercise and Low (Non-hdl-c)-density Lipoproteinsmentioning
confidence: 99%